Investigate A New Tangent Bundle Space from A New Point and Two Curves using MATLAB - Abdel Radi Abdel Rahman Abdel Gadir Abdel Rahman; Makarim Abdullah Mohammed Ali Mohammed (IJRDO -JOURNAL OF MATHEMATICS, 2024)
Our goal was to create a new tangent bundle space from a new point and two curves using the MATLAB program. We used the applied mathematical approach, and we arrived at an accurate model of the tangent bundle space by building an algorithm that implements the solution and displays the results and represents them graphically with ease and with high accuracy. This is what MATLAB makes a suitable working environment for dealing with tangent bundles. Given the importance of tangent bundles in modern engineering and physical sciences, this algorithm can be developed to include the most important areas of tangent bundles instead of the complex traditional method